ANALYSIS OF THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE JOB SATISFACTION AT THE CUSTOMS AND EXCISE SUPERVISION AND SERVICE OFFICE TYPE MADYA CUSTOMS B MEDAN - Maliki Marpaung; Prihatin Lumbanraja; Iskandarini (RADJA PUBLIKA, 2024)
Human resources are very important and cannot be separated from an organization, whether a company or institution. So it can be said that a company is growing rapidly if it has a lot of competent human resources in their field, otherwise if the human resources are not working with quality then the company's development will be hampered. The main problem that often occurs is the management's lack of attention to employee satisfaction which leads to better work implementation. This research aims to determine and analyze the influence of leadership style, organizational commitment and organizational culture on employee performance through employee job satisfaction at the Medan Customs and Excise Supervision and Service Office of Type B Medan. The type of research used is quantitative research. The population used in this research were 133 employees at the Medan Customs and Excise Supervision and Service Office, Type B Medan, using a saturated sampling technique as many as 133 employees. The data analysis technique in this research uses descriptive statistical analysis and structural equation modeling (SEM). The results of this research show that leadership style, organizational commitment and organizational culture have a positive and significant effect on employee job satisfaction. Leadership style, organizational commitment, organizational culture and employee job satisfaction have a positive and significant effect on employee performance. Apart from that, leadership style, organizational commitment and work culture have a positive and significant effect on employee performance through employee job satisfaction at the Customs and Excise Supervision and Service Office Type Madya Customs B Medan.